2023
DOI: 10.1186/s13046-023-02701-5
|View full text |Cite|
|
Sign up to set email alerts
|

CREBZF mRNA nanoparticles suppress breast cancer progression through a positive feedback loop boosted by circPAPD4

Abstract: Background Breast cancer (BC) negatively impacts the health of women worldwide. Circular RNAs (circRNAs) are a group of endogenous RNAs considered essential regulatory factor in BC tumorigenesis and progression. However, the underlying molecular mechanisms of circRNAs remain unclear. Methods Expression levels of circPAPD4, miR-1269a, CREBZF, and ADAR1 in BC cell lines and tissues were measured using bioinformatics analysis, RT-qPCR, ISH, and IHC. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…designed to counteract the main neoplastic hallmark features of BC by sustaining proliferative pathways [31,32], evading growth suppressors/evasion of anti-growth signaling [12], resisting programmed cell death [33][34][35][36][37][38][39][40][41][42], inducing angiogenesis (neovascularization) [43][44][45][46], activating invasion and metastasis [47][48][49], preventing genomic instability, mutation, mitosis/cell cycle deregulation [50], evading/avoiding immune destruction [51] and deregulating autophagy [52,53].…”
Section: Nano-"magic Bullets" In Bc Theranosticsmentioning
confidence: 99%
See 2 more Smart Citations
“…designed to counteract the main neoplastic hallmark features of BC by sustaining proliferative pathways [31,32], evading growth suppressors/evasion of anti-growth signaling [12], resisting programmed cell death [33][34][35][36][37][38][39][40][41][42], inducing angiogenesis (neovascularization) [43][44][45][46], activating invasion and metastasis [47][48][49], preventing genomic instability, mutation, mitosis/cell cycle deregulation [50], evading/avoiding immune destruction [51] and deregulating autophagy [52,53].…”
Section: Nano-"magic Bullets" In Bc Theranosticsmentioning
confidence: 99%
“…Circular RNAs (circRNAs) act as microRNA sponges and regulate gene expression as they are related to the hallmarks of cancer-sustaining signaling pathways, including invasion, recurrence, metastasis, apoptosis, ferroptosis and treatment resistance [117]. Zhou et al (2023) showed that delivering CREBZF mRNA NPs can inhibit BC proliferation and promote apoptosis in both BC tissues and cell lines [32]. These authors have proposed a new circRNA, called circPAPD4, whose expression is low in BC tissues and cells, that acts as a sponge by binding miRNA-1269a to increase the expression of CREBZF, a transcription factor that inhibits the activation of STAT3 pathway, leading to a reduction in cell cycle progression [32].…”
Section: Nanomaterials Used Against Sustained Proliferative Signaling...mentioning
confidence: 99%
See 1 more Smart Citation
“…Development of breast cancer in vivo and in vitro was found to be suppressed when introducing CREBZF mRNA nanoparticles. This contributes to new understandings of therapeutic approaches for breast cancer [ 126 ]. The mRNA translation and stability could be modulated by miRNAs binding to target mRNAs creating a complex with a protein known as Argonaute (AGO) protein [ 127 ].…”
Section: Functions Of Circular Rnamentioning
confidence: 99%
“…Following publication of the original article [ 1 ], an error was identified in the author list. Authors, Boxuan Zhou, Jinhua Xue, Runxin Wu, Hongyu Meng, and Ruixi Li were not recognized as equal contributors and co-first authors.…”
mentioning
confidence: 99%